Extreme Diversity of Mycoviruses Present in Isolates of Rhizoctonia solani AG2-2 LP From Zoysia japonica From Brazil - Picarelli, Maria Aurea S. C.; Forgia, Marco; Rivas, Eliana B.; Nerva, Luca; Chiapello, Marco; Turina, Massimo; Colariccio, Addolorata (Frontiers in Cellular and Infection Microbiology, 2019)
Zoysia japonica, in Brazil, is commonly infected by Rhizoctonia solani (R. solani) in humid and cool weather conditions. Eight isolates of R. solani, previously identified as belonging to the AG2-2 LP anastomosis group, isolated from samples from large path symptoms, were collected from three counties in São Paulo state (Brazil) and investigated for the presence of mycoviruses. After detection of double-strand RNA (dsRNA) in all samples, RNA_Seq analysis of ribosomal RNA-depleted total RNA from in vitro cultivated mycelia was performed. Forty-seven partial or complete viral unique RNA dependent-RNA polymerase (RdRp) sequences were obtained with a high prevalence of positive sense ssRNA viruses. Sequences were sufficiently different from the first match in BLAST searches suggesting that they all qualify as possible new viral species, except for one sequence showing an almost complete match with Rhizoctonia solani dsRNA virus 2, an alphapartitivirus. Surprisingly four large contigs of putative viral RNA could not be assigned to any existing clade of viruses present in the databases, but no DNA was detected corresponding to these fragments confirming their viral replicative nature. This is the first report on the occurrence of mycoviruses in R. solani AG2-2 LP in South America.